SYNTHESIS AND CHARACTERIZATION OF FRUCTOSYLTRANSFERASE FROM Aspergillus oryzae IPT-301 FOR HIGH FRUCTOOLIGOSACCHARIDES PRODUCTION - Cunha, Josivan S.; Ottoni, Cristiane A. [UNESP]; Morales, Sergio A.; Silva, Elda S.; Maiorano, Alfredo E.; Perna, Rafael F. (Brazilian Soc Chemical Eng, 2019)
Fructooligosaccharides (FOS) are mainly produced by microbial fructosyltransferases (FTase, E.C.2.4.1.9), and Aspergillus oryzae IPT-301 has shown high fructosyl transferring and low hydrolytic activities, which leads to high FOS production yields, but the main operating parameters for its best performance have been scarcely studied. Thus, this work aimed to evaluate the cellular growth, production and characterization of mycelial and extracellular FTases by Aspergillus oryzae IPT-301. Experimental design showed that the extracellular FTase performance was optimized (high transfructosylation activity and low hydrolytic activity) for reaction pH 5.5-6.75 and temperature of 45-50 degrees C and was fitted by the Michaelis-Menten model, while the mycelial FTase showed better performance at pH below 6.5 and temperature above 46 degrees C and was better fitted by the Hill model. The results obtained showed that the fungus represents a promising source for FOS production on a laboratorial scale.
Keywords: Aspergillus oryzae IPT-301; Submerged fermentation; Fructosyltransferase; Enzymatic characterization; Fructooligosaccharides